Why public ownership? Urban utilities in London, 1870-1914 - Schapiro, R; Schapiro, R (2003)
Private gas and water companies received parliamentary permission to act as incorporated companies in the early 1800s. Then, the idea that gas and water would be anything other than a luxury was unthinkable, and government regulated by entry. But by the 1830s the problems with competition were clear. Under pressure from the new sanitary reformers, and from the companies themselves, parliament sought new ways to regulate. However, the institutional endowments of the British state did not facilitate a working regulatory regime, and by the 1870s, the regulatory foundations for public ownership had been set.